Metallo-ß-Lactamase Producing Pseudomonas species in a Tertiary Care Hospital of Dhaka City (Bangladesh Journal of Medical Microbiology, 2011)
Among the various beta-lactam antibiotics, carbapenems are the most potent and have been reserved for use in treating infections caused by multi-drug resistant (MDR) Gram negative bacilli, especially Pseudomonas. They are effective even against Extended Spectrum beta-lactamase (ESBL) and Amp C b-lactamase producing bacteria. The clinical utility of carbapenems is under threat with the emergence of carbapenem resistant bacteria due to production of carbapenem hydrolyzing metallo-beta-lactamase (MBL) which confers high-level resistance to all b-lactam antibiotics except aztreonam. The prevalence of MBLs have been studied in many countries but not been reported in Bangladesh. The purpose of the study to determine the presence of MBLs producing Pseudomonas in clinical samples from a tertiary care hospital. MBLs producing Pseudomonas in various clinical samples of an urban hospital of Dhaka city was investigated over a 6-month period (January 2009-June 2009). EDTA-IMP agar dilution minimum inhibitory concentration (MIC) reduction method was employed to detect MBL producing Pseudomonas sp. Out of 44 Pseudomonas isolates 08 (18.2%) were sensitive and 23 (52.3%) were resistant to imipenem while 13 (29.5%) were intermediate resistant (MIC = 8 μg/ml) to imipenem. All Pseudomonas showing intermediate resistance to imipenem were found sensitive by disc diffusion method. MBL phenotype was detected in 43%(10 out of 23) imipenem resistant Pseudomonas spp. while the rate was 61%(08 out of 13) is intermediate resistant strains by EDTA-IMP agar dilution MIC method. The results of the study indicated high prevalence of MBL producing Pseudomonas spp. in our hospital environment. Early detection of these MBL producing Pseudomonas is necessary to institute appropriate treatment and effective infection control measures. Key words: Metallo-ß-lactamase, Pseudomonas species, Gram negative bacilli. DOI: http://dx.doi.org/10.3329/bjmm.v4i1.8469 BJMM 2011; 4(1): 43-45